CRYSTAL FRACTIONATION AND THE EVOLUTION OF INTRA-PLATE HY-NORMATIVE IGNEOUS SUITES: INSIGHTS FROM THEIR FELDSPARS - Nekvasil H.; Simon A.; Lindsley D.H. (My University, 2000)
Feldspars and normative feldspar constituents of bulk magma show trends supportive of fractional crystallization in the three main types of hy-normative intraplate suites that contain qz-oversaturated rocks: ocean island and continental alkalic suites, ocean island tholeiitic suites and continental tholeiitic suites. These suites are characterized by the presence of a single feldspar in each suite member, a shift of this feldspar from plagioclase to alkali feldspar, and K enrichment of alkali feldspar with decreasing temperature in the trachytic members. The modal feldspars provide evidence for a reaction relationship between feldspars and indicate a build-up of magmatic volatile content towards saturation with progressive fractionation of a parental magma having low initial volatile content. The feldspar and normative feldspar evolutionary paths are unique for each of the three suite types but similar for different suites within the same type. This characteristic extends to the felsic members, making it easy to distinguish between rhyolitic or granitic rocks from the different suite types. The feldspars in natural volcanic suites commonly show evidence for a polybaric history, particularly in the least-evolved suite members. Late-stage feldspars of the intermediate members and feldspars of the most evolved members show paths indicative of significantly lower temperature and pressure regimes.